A Paddle-Wheel Motif versus an Extended Network: Two Crystalline Forms of 2, 4-Bis(Phenylamino)Nitrobenzene. (February 2015) - Plater, M. John; Harrison, William T.A.
2, 4-Difluoronitrobenzene is reacted with either one or two amines selected from aniline, ammonia, butylamine and benzylamine. All products are characterised spectroscopically and by single-crystal structure determinations. When formed as a minor component alongside 4-dimethylamino-2-(phenylamino)nitrobenzene, 2, 4-bis(phenylamino)nitrobenzene crystallises as a hydrogen-bonded hexamer, or paddle-wheel motif, encompassing one-dimensional channels, but as a dense framework when pure. 2, 4-Bis(butylamino)nitrobenzene crystallises with the same hexamer motif but with offset sheets.